Racial Essentialism and Stress: A Deadly Combination for Prospective Police Officers’ Encounters with Black Suspects - Tawa, John (Race and social problems, 2023)
Previous research based on documented incidents of police uses of lethal force and experimental studies using computer sorting programs have demonstrated that incorrect lethal force decisions tend to occur more frequently with Black relative to White suspects. Using virtual reality, the current study examined the psychophysiology underlying incorrect lethal force decision with Black suspects, and the interactive impact of racial essentialism. Forty-nine White criminal justice majors viewed 360 degree videos of high-pressure suspect interactions in VR, from the perspective of the police officer. A virtual police-issued handgun was used to make and record decisions to shoot; incorrect uses of lethal force were operationalized using signal detection theory. Physiological stress (i.e., variance in pupil dilation) and visual attention were measured with embedded eye tracking in the VR. As predicted, physiological stress led to more incorrect uses of lethal force with Black suspects through fixated visual attention, but only among those who scored high on a racial essentialism survey measure. Findings converge with more recent studies supporting the potent interactive role between cognition (e.g., racial essentialism) and affect (i.e., stress) on lethal force decisions with Black suspects. These studies point to the continued role of psychoeducation and cognitive–behavioral interventions in informing police training interventions aimed at mitigating incorrect uses of lethal force with Black men and women.